2020
DOI: 10.3389/fnhum.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Directional Deep Brain Stimulation on Sensory Thresholds in Parkinson’s Disease

Abstract: Objective: Previous studies showed that deep brain stimulation (DBS) relieves pain symptoms in Parkinson disease (PD) patients when programmed for motor-symptom relief. One factor involved in pain processing is sensory perception of stimuli. With the advent of directional leads, we explore whether directional DBS affects quantitative sensory testing (QST) metrics acutely. Methods: PD patients with subthalamic (STN) DBS and directional leads were tested in 5 settings (DBS-OFF, DBS-ON with omnidirectional stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Finally, the lack of statistical power due to small sample sizes might have contributed to different results as well. However, in addition to studies that investigated tactile perception of the foot, there are a number of studies that analyzed tactile perception at other anatomical locations in PD, including the arms, hands, fingers, and the torso [32][33][34][36][37][38]81,90]. Most of these studies found that PD increases tactile perception thresholds, which confirms the results of our study.…”
Section: Plantar Cutaneous Vibration Perceptionsupporting
confidence: 89%
See 3 more Smart Citations
“…Finally, the lack of statistical power due to small sample sizes might have contributed to different results as well. However, in addition to studies that investigated tactile perception of the foot, there are a number of studies that analyzed tactile perception at other anatomical locations in PD, including the arms, hands, fingers, and the torso [32][33][34][36][37][38]81,90]. Most of these studies found that PD increases tactile perception thresholds, which confirms the results of our study.…”
Section: Plantar Cutaneous Vibration Perceptionsupporting
confidence: 89%
“…DBS-induced gait improvements might also be associated with enhanced lower limb muscle strength, the normalization of leg muscle contraction patterns, and inter-limb coordination [125,141,167,212,226,252,255,259,[262][263][264]. As hypothesized in this study, the normalization of proprioceptive functionality and enhanced processing and sensory-motor integration of afferent information through DBS may have additionally caused enhanced gait performance [19,[32][33][34]36,74,90,91,265,266].…”
Section: Gaitmentioning
confidence: 55%
See 2 more Smart Citations
“…None of them found them to be worse. This positive attitude is only partially reflected by the literature with most papers showing theoretical but no clinical benefits ( Rammo et al, 2021 ; Bruno et al, 2021 ; Steffen et al, 2020 ; Shao et al, 2020 ; Rebelo et al, 2018 ; Schnitzler et al, 2022 ; Sabourin et al, 2020 ; Dembek et al, 2017 ; Steigerwald et al, 2016 ) and only very few showing some benefit ( Krüger et al, 2021a ; Hurt et al, 2023 ; Pintér et al, 2023 ). However, most of these studies are on newly implanted patients with short follow-up times, and the discrepancy could well reflect a gap in the literature that may be filled over time.…”
Section: Discussionmentioning
confidence: 99%